Assessing adhesive remnant removal and enamel damage with ultraviolet light: An in-vitro study - Ribeiro, Alexandre Antonio; Almeida, Layene Figueiredo [UNESP]; Martins, Lidia Parsekian [UNESP]; Martins, Renato Parsekian [UNESP] (Elsevier B.V., 2017)
Introduction: Our objective was to assess the amounts of adhesive remnant and enamel damage when removing composite under conventional lighting and ultraviolet (UV) light. Methods: Thirty-eight premolars were divided into 2 groups according to the lighting used for adhesive removal. A multifluted tungsten-carbide bur at low speed was used for this process in both groups. The UV group received conventional lighting associated with UV light, and the conventional group received conventional lighting only. The amounts of adhesive remnant were calculated using images of the teeth taken under UV light with software. Scanning electron microscopy images of epoxy adhesive replicas of the teeth made before bonding and after adhesive removal were graded according to the enamel damage index (EDI), and the difference between the final and initial EDI scores was used for assessment of the enamel damage. To detect differences between the groups, the Mann-Whitney test was used to analyze the data from the adhesive remnant index and the EDI. Results: The conventional group had more adhesive left on the enamel (P <0.001) than did the UV group. There was no difference between groups for the EDI (P = 0.729). Conclusions: UV lighting allows significantly more adhesive removal without increasing the damage caused to the enamel.